The Impact of Cage Dimensions, Positioning, and Side of Approach in Extreme Lateral Interbody Fusion. Issue 1 (February 2018) - Alimi, Marjan; Lang, Gernot; Navarro-Ramirez, Rodrigo; Perrech, Moritz; Berlin, Connor; Hofstetter, Christoph P.; Moriguchi, Yu; Elowitz, Eric; Härtl, Roger
Abstract : Study Design: This is a retrospective single-center study. Objective: The aim of the study was to evaluate the impact of cage characteristics and position toward clinical and radiographic outcome measures in patients undergoing extreme lateral interbody fusion (ELIF). Summary of Background Data: ELIF is utilized for indirect decompression and minimally invasive surgical treatment for various degenerative spinal disorders. However, evidence regarding the influence of cage characteristics in patient outcome is minimal. Materials and Methods: Patients undergoing ELIF between 2007 and 2011 were included in a retrospective study. Demographic and perioperative data, as well as cage characteristics and side of approach were extracted. Radiographic parameters including lumbar lordosis, foraminal height, and disc height as well as clinical outcome parameters (Oswestry Disability Index and Visual Analog Scale) were measured preoperatively, postoperatively, and at the latest follow-up examination. Cage dimensions, in situ position, and type were correlated with radiographic and clinical outcome parameters. Results: In total, 84 patients with a total of 145 functional spinal units were analyzed. At the last follow-up of 17.7 months, radiographic and clinical outcome measures revealed significant improvement compared with before surgery with both, 18 and 22 mm cage anterior-posterior diameter subgroups ( P ⩽0.05). Among cage characteristics, 22 mm cages presented superior restoration of foraminal and disc heights compared with 18 mm cages ( P ⩽0.05). Neither position of the cage (anterior vs. posterior), nor the type (parallel vs. lordotic) had a significant impact on restoration of foraminal height and lumbar lordosis. Moreover, the side of surgical approach did not influence the amount of foraminal height increase. Conclusions: Cage anterior-posterior diameter is the determining factor in restoration of foraminal height in ELIF. Cage height, type, positioning, and side of approach do not have a determining role in radiographic outcome in the present study. Sustainable foraminal height restoration is achieved by implantation of wider cages. Level of Evidence: Level 3. Abstract : Supplemental Digital Content is available in the text.